Effects of alkaline activators on pore structure and mechanical properties of ultrafine metakaolin geopolymers cured at room temperature. (26th December 2022) - Luo, Yiping; Jiang, Zhonghua; Wang, Defa; Lv, Yurong; Gao, Cungen; Xue, Guobin
Highlights: Fast-hardening early-strength geopolymers fabricated at ambient temperature. The product of geopolymer made with UMK has only the NASH phase. With the increase of sodium hydroxide concentration, the internal macropores of UMK geopolymer gradually evolved into mesopores. The time for UMK geopolymer to reach optimum strength is related to sodium hydroxide concentration. Abstract: Geopolymer is a new type of green gelling and environmental protection material, but the curing temperature limits the application of geopolymer in the construction industry. In this paper, the effects of NaOH on the pore structure and mechanical properties of ultrafine metakaolin (UMK) geopolymers under room temperature curing conditions were investigated. In this experiment, different concentrations of alkaline activators were prepared by changing the concentration of NaOH in the composite alkaline activator, and geopolymers were prepared with different alkaline activators and UMK. Different UMK geopolymers have been extensively analyzed to characterize their pore distribution, pore structure, and mechanical properties. The relationship between NASH gel and NaOH concentration was quantified by simultaneous thermal analysis (TG-DTG) and X-ray diffraction (XRD). The evolution of pore distribution and pore structure of UMK geopolymers with NaOH concentration was characterized by scanning electron microscopy (SEM) and proton nuclear magnetic resonance spectroscopy ( 1 H NMR). The results show that UMK only generates the NASH phase in the geopolymerization reaction. With the increase of sodium hydroxide concentration, the formation of NASH gel increases, and the crystallinity of the sample increases. SEM and 1 H NMR results show that the UMK geopolymer prepared with a high concentration of NaOH is fully hydrated and has a dense structure. Through comparative analysis of UMK geopolymer pore distribution and pore structure characteristics, it was found that the porosity of UMK geopolymer decreased with the increase of sodium hydroxide concentration. The proportion of small pores did not change much, while the large pores gradually evolved into mesopores. In addition to this, curing time was found to have no significant effect on geopolymer microstructure and strength development. This research provides a theoretical basis for the practical engineering application of UMK.